Relationship of Teacher’s Role and Nutrient Intake with Obesity in Elementary School Student at Medan Maimun Sub-district, Indonesia - Desty Adinda; Etti Sudaryati; Evawany Aritonang; Ernawati Nasution (Budapest International Research and Critics University, 2019)
Obesity is a problem of excessive fat accumulation and has a serious effect on health. The prevalence of overweight and obesity are in the children to increase significantly in the world. The objectives of this research are to analyze the relationships between teacher’s role and nutrient intake with obesity in elementary school student at Medan Maimun Sub-district. The research design uses a cross-sectional study, has taken location at Elementary School in Medan Maimun sub-district. Samples were taken by simple random sampling of 120 students. Data were collected by using questionnaires, form food recall 2x24 hours, and BMI for age. Data analyzed using Chi-Square test. The result showed as 22,5% children were obese; the teacher’s role were majority low (75%), and energy intake is under intake level Recommended Daily Allowance (55%). Bivariate analysis showed there is relation between teacher’s role with obesity (p=0.008), energy intake (p=0.007) and fat intake (p=0.038) with obesity. Intake of protein (p=0.739) and carbohydrate (p=0.540) are not related with obesity. The management of obesity in children is recommended to change children’s diet and lifestyle with family and teachers support at school.